2021
DOI: 10.1002/lary.29581
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Incidental Mastoid Opacification and the Need for Intervention: A Meta‐Analysis

Abstract: Objectives/Hypothesis: The increasing use of cross-sectional imaging has led to the predicament of incidental mastoid opacification (IMO). We investigated the prevalence of IMO and the clinical need for ENT assessment or intervention when identified.Study Design: Systematic review and meta-analysis. Methods: The PRISMA statement standards were used to search electronic databases including Medline, Embase, PubMed, and Web of Science. The selection criteria were mastoid opacification found on computed tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Mastoiditis is a frequent incidental radiological finding on CT of the head, as fluid collects in mastoid air cells whilst the patient lies supine as the scan is performed. 25 Mughal et al . reported that 8.4 per cent of head CT scans suggested incidental mastoid opacification.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Mastoiditis is a frequent incidental radiological finding on CT of the head, as fluid collects in mastoid air cells whilst the patient lies supine as the scan is performed. 25 Mughal et al . reported that 8.4 per cent of head CT scans suggested incidental mastoid opacification.…”
Section: Discussionmentioning
confidence: 99%
“…Marginally lower rates of sinus and mastoid opacification in patients with Covid-19 are reported in the literature (Table 6); [25][26][27][28][29][30] 41.8 per cent of Moonis and colleagues' cohort of 55 patients had sinus disease, yet only 7 per cent demonstrated mastoid opacification. 29 Similarly, İslamoğlu et al reported much lower levels of mastoid opacification in a cohort of 129 patients, at only 2.32 per cent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations